2009
DOI: 10.1002/j.1556-6678.2009.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

The Adolescent Mattering Experience: Gender Variations in Perceived Mattering, Anxiety, and Depression

Abstract: Individuals who perceive that they matter to others are likely to experience lower anxiety and depression levels. The effects of young adolescents' perceived mattering on their anxiety and depression levels were examined. Results indicated that female adolescents reported lower anxiety levels but greater depression levels than did male adolescents, perceived mattering was inversely related to adolescents' anxiety and depression levels, and the associations between mattering and anxiety and between mattering an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 29 publications
1
39
0
2
Order By: Relevance
“…In fact, research indicates that individuals with a strong sense of mattering tend to have a positive self-esteem (Pearlin and LeBlanc 2001), and a greater sense of well-being (Thoits 2012). Those with low levels of mattering are more likely to experience depression and anxiety (DeForge and Barclay 1997; Dixon, Scheidegger, and McWhirter 2009;Marcus 1991;Rayle 2005;Rosenberg and McCullough 1981). Further, adolescents who feel as though they do not matter are more likely to engage in suicide ideation (Elliot, Colangelo, and Gelles 2005).…”
Section: Matteringmentioning
confidence: 95%
“…In fact, research indicates that individuals with a strong sense of mattering tend to have a positive self-esteem (Pearlin and LeBlanc 2001), and a greater sense of well-being (Thoits 2012). Those with low levels of mattering are more likely to experience depression and anxiety (DeForge and Barclay 1997; Dixon, Scheidegger, and McWhirter 2009;Marcus 1991;Rayle 2005;Rosenberg and McCullough 1981). Further, adolescents who feel as though they do not matter are more likely to engage in suicide ideation (Elliot, Colangelo, and Gelles 2005).…”
Section: Matteringmentioning
confidence: 95%
“…For more than 2 decades, the concept of mattering, “the individual's feeling that he or she counts, makes a difference” (Rosenberg, , p. 215), has been studied in many disciplines, including social psychology (e.g., Elliott, Kao, & Grant, ), adolescent studies (e.g., Marshall, ; Rayle, ), education (e.g., A. L. Dixon & Tucker, ), and counseling (e.g., Powers, Myers, Tingle, & Powers, ). Many researchers who studied adolescents and young adults, such as A. L. Dixon, Scheidegger, and McWhirter () and S. K. Dixon and Kurpius (), have found that a higher sense of mattering is associated with better mental health outcomes among this population. On college campuses, mattering has been used to predict a student's adjustment to the college environment (Schlossberg, Lassalle, & Golec, ; Tovar, Simon, & Lee, ).…”
mentioning
confidence: 99%
“…Yet other researchers (e.g., Dixon, 2007; Dixon, Scheidegger, & McWhirter, 2009; Taylor & Turner, 2001), not focused expressly on intimate relationships, showed that mattering to friends and peers inversely affected depressive symptoms. Using data from a large urban community sample in Canada (n = 1,300), Taylor and Turner (2001) showed that women and men, ages 18-55, who reported higher levels of mattering experienced fewer depressive symptoms.…”
Section: Introductionmentioning
confidence: 87%